2019
DOI: 10.24959/cphj.19.1485
|View full text |Cite
|
Sign up to set email alerts
|

Circadian developmental rhythms of the experimental paracetamol hepatitis and the effect of hepatoprotectors on the activity of pro-oxidative / antioxidant and cytolytic processes

Abstract: Національний фармацевтичний університет Інститут підвищення кваліфікації спеціалістів фармації Національного фармацевтичного університету* Вищий державний навчальний заклад України «Буковинський державний медичний університет»** Циркадіанні ритми розвитку експериментального парацетамолового гепатиту та впливу гепатопротекторів на активність прооксидантно/антиоксидантних і цитолітичних процесів Одним із актуальних напрямків сучасної експериментальної та клінічної фармакології є визначення залежності ефективност… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Throughout the study, there was a progressive increase in TBA-AP content in both tissues, the maximum values of which were recorded on the 10th day of the experiment. Our experimental data are consistent with the results of studies by other authors, which showed that paracetamol poisoning activates the processes of free radical oxidation in animals [21,22].…”
Section: Discussion Of Research Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Throughout the study, there was a progressive increase in TBA-AP content in both tissues, the maximum values of which were recorded on the 10th day of the experiment. Our experimental data are consistent with the results of studies by other authors, which showed that paracetamol poisoning activates the processes of free radical oxidation in animals [21,22].…”
Section: Discussion Of Research Resultssupporting
confidence: 93%
“…When comparing the indicators of lipoperoxidation with the indicators of oxidative modification of proteins, there was a tendency to increase them after the defeat of paracetamol. This confirms the relationship and interdependence of these processes in the development of pathological conditions, which is given in other experimental works [21,22].…”
Section: Discussion Of Research Resultssupporting
confidence: 91%
“…According to a number of studies on the use of antral, the remedy promotes the restoration of glycogen and protein-synthesizing function of the liver, improves phospholipid synthesis, activates cytochrome system, stimulates tissue respiration processes, improves energy supply and functioning of hepatocyte monooxygenase system, contri buting to the reduction of endotoxicosis intensity [11,12]. By inhibiting cyclooxygenase and reducing the synthesis of prostaglandins and other mediators of inflammation, antral exerts its anti-inflammatory effect, inhibiting the processes of free radical oxidation and enhancing the processes of neutralization of free radicals, leading to a decrease in the severity of cytolytic syndrome that prevents the destruction of hepatocytes and reduces the intensity of the inflammatory process in the bronchi [13].…”
Section: Introductionmentioning
confidence: 99%